2021
DOI: 10.1186/s12884-021-03832-3
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone levels on the human chorionic gonadotropin trigger day affect the pregnancy rates for embryos transferred at different stages of development in both general and selected IVF/ICSI populations

Abstract: Background Two meta-analyses have shown that pregnancy and birth rates are significantly higher after blastocyst transfer than after cleaved embryo transfer. Other studies have revealed that a serum progesterone level > 1.5 ng/ml on the trigger day is responsible for premature luteinization and is associated with a low pregnancy rate. The objectives of this retrospective study were to determine whether blastocyst transfer gave higher pregnancy rates than cleaved embryo transfer at day 3 in b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The difference with our study is that the difference the team got was more pronounced than ours and statistically significant. Merviel et al (28) in the same vein with our findings showed that serum progesterone level was significantly lower among pregnant women compared to non-pregnant (p <0.01) and that progesterone follicular index of >0.6 and progesterone oocyte index of >0.36/ng/ml/oocyte were more predictive of lower pregnancy rate, thus bringing to fore the correlating nature of both numbers of oocytes retrieved and numbers of follicles above 14mm on HCG day to progesterone level. It differed from our study in that cut-off value used for progesterone was 0.9ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…The difference with our study is that the difference the team got was more pronounced than ours and statistically significant. Merviel et al (28) in the same vein with our findings showed that serum progesterone level was significantly lower among pregnant women compared to non-pregnant (p <0.01) and that progesterone follicular index of >0.6 and progesterone oocyte index of >0.36/ng/ml/oocyte were more predictive of lower pregnancy rate, thus bringing to fore the correlating nature of both numbers of oocytes retrieved and numbers of follicles above 14mm on HCG day to progesterone level. It differed from our study in that cut-off value used for progesterone was 0.9ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…First, there has been robust evidence that LFEP impairs endometrial receptivity, but LFEP in the fresh cycle does not affect the cumulative birth rate of the frozen transfers in a freeze-only approach (18). A freeze-all policy should be proposed for LFEP patients to avoid the adverse impact of LFEP (19)(20)(21). We agree with the conclusion that LFEP has deleterious impact on fresh embryo transfers, but we should also be cautious regarding the cost of a freeze-all policy, especially for good-prognosis patients with sufficient high-quality embryos.…”
Section: Discussionmentioning
confidence: 99%
“…2) The progesterone to oocyte index (POI), i.e., the relative value of the ratio of progesterone to aspirated oocytes. A high POI predicts poor clinical pregnancy and live birth rates in fresh IVF/ICSI cycles ( 22 ). Extreme situations, such as early ovulation, due to which a very few oocytes are obtained on the day of egg retrieval, might have affected the results.…”
Section: Methodsmentioning
confidence: 99%